4(x-4)=5614

Reduce the expression 5614 by cancelling the common factors.

Factor 14 out of 56.

4(x-4)=14⋅414

Factor 14 out of 14.

4(x-4)=14⋅414(1)

Cancel the common factor.

4(x-4)=14⋅414⋅1

Rewrite the expression.

4(x-4)=41

4(x-4)=41

Divide 4 by 1.

4(x-4)=4

4(x-4)=4

Divide each term in 4(x-4)=4 by 4.

4(x-4)4=44

Cancel the common factor of 4.

Cancel the common factor.

4(x-4)4=44

Divide x-4 by 1.

x-4=44

x-4=44

Divide 4 by 4.

x-4=1

x-4=1

Add 4 to both sides of the equation.

x=1+4

Add 1 and 4.

x=5

x=5

Solve for x 4(x-4)=56/14